Continuous/lifelong learning and educational infrastructure: urban study - Posțan, Liliana (Pedagogika Społeczna Nova, 2023)
In this article, we refer to lifelong learning infrastructure, as can be oberved and accessed by the subjects of this study near their home/location, in accordance with the recommendations of the Memo- randum on Lifelong Learning.1 In order to estimate the accessibility and access to education and lifelong learning, we conducted a case study on a street in Chisinau. We note that in the Republic of Moldova, the processes of educa- tion reform through modernization have focused mainly on intellectual aspects (curriculum, teacher training, textbook reform), while “material”/infrastructure aspects (training environment and means of education) were given less attention, citing lack of financial means or division of responsibility between authorities at different levels. In this context, we note that in 2020, Chisinau, along with 54 other cities in 27 countries around the world, joined the UNESCO Global Network of “Learning Cities”. Selected cities are outstanding examples of locations where lifelong learning can become a local reality. We analyze development strategies at different levels in order to pursue the objectives related to ensuring quality education from the perspective of lifelong learning.